Mechanical and Microstructural Properties of Sheep Hydroxyapatite (SHA)-Niobium Oxide Composites - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2012)
The aim of this study is to produce and to investigate the mechanical and microstructural properties of composite materials made of hydroxyapatite, obtained from natural sheep bone and niobium oxide (5 and 10 wt%). Sheep hydroxyapatite (SHA) matrix was reinforced with 5 and 10 wt% of niobium (Nb) oxide powder. The calcinated SHA was ball milled separately with 5% and 10% niobium oxide for 4 h. The samples were subjected to sintering at different temperatures between 1000 degrees C and 1300 degrees C. The mechanical properties were determined by measuring compression strength and Vickers microhardness (HV). X-ray diffraction and scanning electron microscopy studies were carried out to analyze the microstructure. With increasing sintering temperature, mechanical properties of composites increased. The SHA-composites with 10 wt% niobium oxide addition had better mechanical properties at all sintering temperatures. The highest mechanical properties were obtained in SHA-10 wt% niobium oxide composite sintered at 1300 degrees C. Adding of niobium oxide to SHA could be a valuable method to produce rigid and high load carrying ability HA composite which is suitable for orthopedic applications.